Descartes in a 'Headstand': Introducing 'Body-Oriented Pedagogy' - Ergas, Oren (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2013)
This article's main theme is the conceptualization of a 'body-oriented-pedagogy' that unfolds a possible account of 'how one learns from the body'. Based on B.K.S Iyengar's approach to yoga-posture practice, which is embedded in classical yoga's philosophy of 'mind', a 'body-oriented pedagogy' is depicted as a practice that seeks to incite 'embodied mindfulness'. The pedagogy trains one in turning 'body' into 'subject', thus quieting the 'thinking mind'. It is thus conceptualized as turning the Cartesian crowning of ‘mind’ over ‘body’ upside down. This pedagogy is suggested as yielding 'education towards and in presence'. Presence is characterized as a mode of perceiving experience prior to the grid of language and concepts, enhancing one's ability to choose one’s action. Applying the grounding of pedagogy in ‘body’, the article then contributes to the discourse involved in the incorporation of contemplative practice within schooling. 'Body-oriented pedagogy' is depicted as compatible with both 'spiritual' and 'non-spiritual' curriculum orientations.